From one transformation to another - Glowacki, Michal; Kuś, Michal (MediaAcT/Erich Brost Institute, 2011)
This report on innovations of media accountability and transparency in Serbia underlines the main tendencies related to the current discussions on the challenges for media in an era of social changes and technological development. On the basis of available literature and the interviews conducted with Serbian media experts, scholars and practitioners in Belgrade (December 2010) several trends have been observed. Hence, the paper deals with cultural, social and political context, the level of journalistic professionalization as well as the effectiveness and legitimacy of existing media accountability and transparency institutions. An in-depth analysis of the development of new media platforms and Internet users’ culture helps to define some of most significant examples of external and internal practices, strategies and cases maintaining media accountability and transparency in the online space. The research on the usage of social networks and blogs, as well as on practices fostering actor and production transparency as well as the level of media responsiveness underlines the current stage and future scenario of the evolution of system making Serbian media organizations accountable and transparent.
Towards an understanding of challenges for media accountability online in Serbia
MediaAcT Working Paper;9/2011
Keywords: Accountability; Ethics; Europe; Internet; Journalism; Media; Online; Responsiveness; Serbia; Social Media; Transparency; 070; Glaubwürdigkeit; Journalismus; Massenmedien; Serbien; Soziale Software